2018
DOI: 10.1016/j.parkreldis.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

An updated diagnostic approach to subtype definition of vascular parkinsonism – Recommendations from an expert working group

Abstract: This expert working group report proposes an updated approach to subtype definition of vascular parkinsonism (VaP) based on a review of the existing literature. The persistent lack of consensus on clear terminology and inconsistent conceptual definition of VaP formed the impetus for the current expert recommendation report. The updated diagnostic approach intends to provide a comprehensive tool for clinical practice. The preamble for this initiative is that VaP can be diagnosed in individual patients with poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 54 publications
0
47
0
3
Order By: Relevance
“…These patients were followed up for three and ten years and a clinical diagnosis was established by two expert neurologists in movement disorders based on a repeated structured interview and extensive neurological examination. In 2018, twelve years after inclusion, all diagnoses were re-evaluated and updated according to the most recent clinical criteria (12)(13)(14)(15)(16)(17), disease course based on the patients' medical files, follow-up visits and neuropathological examination whenever available Disease severity and cognitive function were evaluated using the Hoehn and Yahr (HY) scores, the Unified Parkinson's Disease Rating Scale (UPDRS), the International Cooperative Ataxia Rating Scale (ICARS) and the Mini-Mental State Examination (MMSE). Disease progression was assessed by subtracting the score at follow-up from the score at baseline and dividing by years of follow-up (∆t = 3 years) ( Table 1).…”
Section: Patientsmentioning
confidence: 99%
“…These patients were followed up for three and ten years and a clinical diagnosis was established by two expert neurologists in movement disorders based on a repeated structured interview and extensive neurological examination. In 2018, twelve years after inclusion, all diagnoses were re-evaluated and updated according to the most recent clinical criteria (12)(13)(14)(15)(16)(17), disease course based on the patients' medical files, follow-up visits and neuropathological examination whenever available Disease severity and cognitive function were evaluated using the Hoehn and Yahr (HY) scores, the Unified Parkinson's Disease Rating Scale (UPDRS), the International Cooperative Ataxia Rating Scale (ICARS) and the Mini-Mental State Examination (MMSE). Disease progression was assessed by subtracting the score at follow-up from the score at baseline and dividing by years of follow-up (∆t = 3 years) ( Table 1).…”
Section: Patientsmentioning
confidence: 99%
“…Orimo et al [12] reported a 68-year-old male with FD (Gb3 deposits in cardiac and kidney autopsy, but without genetic investigation) presenting an atypical form of parkinsonism, beginning at the age of 63 years old, with axial signs (gait and postural instability), mild symmetrical rigidity, and pyramidal signs (mild right hemiparesis, generalized hyperreflexia and positive Babinski sign on both sides). Brain MRI showed multiple T2 hyperintensities in the basal ganglia and deep white matter regions, suggesting the possibility of vascular and/or neuronal dysfunction in FD [24]. Buechner et al [13] reported a 57-year old woman with FD due to the p.R301P GLA gene mutation, with low leukocyte ␣-Gal A activity (8 nmol/mg per hour), cardiac (left ventricular hypertrophy) and kidney impairment (microalbuminuria of 31.4 g/mL), presenting mild parkinsonism beginning at the age of 46 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless larger studies are needed to confirm our results. Regarding the diagnosis of VP, recent recommendations propose three subtypes: post-stroke VP, insidious VP and mixed PD/CVD (Rektor et al 2018 ). While post-stroke VP patients were formally excluded from our study we used modified Zijlman’s criteria to diagnose VP patients, which fit criteria for the insidious VP subtype.…”
Section: Discussionmentioning
confidence: 99%